2021
DOI: 10.1111/jam.15122
|View full text |Cite
|
Sign up to set email alerts
|

Australian bush medicines harbour diverse microbial endophytes with broad‐spectrum antibacterial activity

Abstract: Aims: Microbial endophytes produce specialized metabolites, including antibiotics and other compounds of pharmaceutical and agricultural value. This study aimed to investigate the diversity and bioactivity of endophytes from medicinal plants used by the Dharawal People of Gamay (Botany Bay), Australia. Methods and Results: Of the 48 endophytes isolated, 19 tested positive for polyketide synthase or non-ribosomal peptide synthetase genes via a PCR incorporating degenerate primers. The biosynthetically talented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Especially, Rhizobiales participate in beneficial interactions with plants, inducing the nodule organogenesis and fixing atmospheric N 2 for better growth , Sphingomonadales are also considered PGPR due to their ability of fixing atmospheric N 2 in symbiosis with plants . The most ten significant changes in abundance after Fe-based NMs and EDTA-Fe treatments showed that Fe–P NMs significantly increased the relative abundances of four bacteria species ( Ramlibacter , Allorhizobium , Arcticibacter , and Amaricoccus ) but decreased six bacteria species (e.g., Sphingomonas and Iamia ) (Figure c,d, Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, Rhizobiales participate in beneficial interactions with plants, inducing the nodule organogenesis and fixing atmospheric N 2 for better growth , Sphingomonadales are also considered PGPR due to their ability of fixing atmospheric N 2 in symbiosis with plants . The most ten significant changes in abundance after Fe-based NMs and EDTA-Fe treatments showed that Fe–P NMs significantly increased the relative abundances of four bacteria species ( Ramlibacter , Allorhizobium , Arcticibacter , and Amaricoccus ) but decreased six bacteria species (e.g., Sphingomonas and Iamia ) (Figure c,d, Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…63 Bacillales are well-known for their antibacterial abilities, which secrete antibacterial substances such as antimicrobial nonribosomal peptides and polyketides to deter invading pathogens, and thus are widely used as biological control agents for agriculture management. 64,65 Sphingomonadales are also considered PGPR due to their ability of fixing atmospheric N 2 in symbiosis with plants. 66 The most ten significant changes in abundance after Fe-based NMs and EDTA-Fe treatments showed that Fe−P NMs significantly increased the relative abundances of four bacteria species (Ramlibacter, Allorhizobium, Arcticibacter, and Amaricoccus) but decreased six bacteria species (e.g., Sphingomonas and Iamia) (Figure 4c,d, Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicate that Australian bush medicines encompass a variety of microbial endophytes with notable biosynthetic capabilities. These microbial endophytes offer potential as antibacterial agents, highlighting their promising application in therapeutic contexts [17].…”
Section: Introductionmentioning
confidence: 99%